Cardiac Histopathology Alterations Induced by Subchronic Mangosteen Rind Extract in Wistar Rats - Ratwita, Welly; Nurrokhmawati, Yanti; Maheswari, Endah Nabilah (Universitas Islam Bandung, 2024)
Mangosteen (Garcinia mangostana L.) is renowned for its potent antioxidant characteristics, including free radical scavenging, and its antibacterial, antifungal, anti-inflammatory, and antidiabetic properties. This study aims to assess the subchronic toxicity effects of ethanol extract from mangosteen rind on the cardiac histopathology of male and female Wistar rats. This research was a posttest-only control group design. Forty biological specimens from 40 Wistar rats were divided into four groups, a control group, and three treatment groups, which were given ethanol extract of mangosteen rind with doses of 250 mg/kg, 500 mg/kg, and 1,000 mg/kg for 28 days. Cardiac specimens were prepared and examined using hematoxylin-eosin (HE) staining at the Anatomical Pathology Laboratory of Universitas Jenderal Achmad Yani in December 2021. The findings indicated that prolonged ingestion of large amounts of ethanol extract from mangosteen rind can cause toxic effects characterized by an inflammatory response in cardiac tissue. No fibrosis or hypertrophy was detected; however, inflammatory changes such as the presence of inflammatory cells, vacuolar changes, and neovascularization were observed. The inflammation observed might be due to excessive antioxidant administration leading to oxidative stress. Inflammatory cells may trigger fibrotic remodeling in the heart. The difference in the quantity of inflammatory cells between male and female rats suggests that gender influences the inflammatory response. Overall, administration of ethanol extract from mangosteen rind at doses of 250 mg/kg, 500 mg/kg, and 1,000 mg/kg cause subchronic toxicity effects on the heart histopathology of Wistar rats, marked by inflammation.